Diretrizes para elaboração de inventários de emissões de gases de efeito estufa em municípios de pequeno e médio porte - Almeida, Rodrigo de (2011)
With the purpose of mitigating impacts associated to climate changes, the United Nations Framework Convention on Climate Change (UNFCCC) was created in 1992. Since then, countries have been seeking feasible ways of reducing Greenhouse Gas Emissions (GHG) in the atmosphere. In this context, the development of a GHG inventory is the primary stage to establish a national public policy of mitigation and adaptation to climate changes. Presently, there are various methodologies internationally employed in the preparation of inventories; however, there are certain recommendations when the public sector is involved, namely: IPCC References (2006) and the international ISO 14064. Recently, the World Bank, in partnership with UNEP, started to design a draft standard for GHG inventories in the public sector. This paper presents guidelines and tools for preparing GHG inventories in the public sector. The main objective is to suggest a simplified script for GHG inventories of small and medium-sized municipalities. The work was subdivided into three stages: concept, development and consolidation. At the first stage, the activities to be developed were planned and outlined. At the second stage, an analysis of the IPCC References (2006) and a field survey with public authorities of cities conurbed to Curitiba were carried out. Finally, at the third stage, a simulation of the GHG inventory was performed using data and information of the municipality of Campo Magro, based on the simplified inventory script proposed and with the support of the C-FAR tool, adapted to the national reality. The final result of this process was a simplified script for the preparation of a GHG inventory in small and medium-sized municipalities, based on IPCC References (2006). The production of GHG inventories at a municipal scale, especially in small and medium-sized municipalities, is a great challenge in the public management process, because the lack of technical and financial resources, the inexistence of a specific legislation about the matter and the absence of prepared public managers represent a large barrier to be overcome in the mitigation and adaptation to climate changes.